The shear strength of soft clay reinforced with group crushed brick columns - Yong Ler, Low (2018)
The construction industry in Malaysia has been generating tons of construction waste which will then be thrown into the landfills. Waste in construction sites are generated due to defective materials, wastage and leftover after works. The sources of waste generation in construction activities are rarely taken seriously by the contractors in Malaysia. The unavoidable generated waste should be turned to an economical effective product, which can help in generating new income for a project, at the same time reduce its destructive impact to the environment. To stabilize the problematic soft clay with the brick waste generated in construction activities by using stone column soil improvement method can be a method to reduce the construction waste at the same time improve the soil condition. Crushed brick particles forming columns are designed to increase the permeability of soft clay, which can help in accelerating the consolidation process and decrease the compressibility of soil. This is also expected to increase the shear strength and bearing capacity of soil, making it more suitable for construction activities. There are tree batches with 21 samples undergo Unconfined Compression Test. Each batch includes sample of clay reinforced with brick columns with penetration ratio of 0.6, 0.8, 1.0, for both 10mm and 16mm columns, and a sample without any reinforcement. The sample without any reinforcement is used as the controlled sample to determine the shear strength of unreinforced sample for comparison use. The kaolin specimens are inserted into the mould and being drilled for columns installation. The holes for the columns are drilled with drill bits of 10mm and 16mm diameter for the respective depths. The crushed brick poured into the pre-drilled hole from 10mm above the surface of clay specimen for three layers. The result shows that the improvement shear strength for height penetration ratio of 1.0 is 13.33% which was the highest, while 0.6 and 0.8 are 12.31% and 9.79% respectively for group crushed brick columns with diameter 10mm. The improvement of shear strength is highest for height penetration ratio of 1.0 with 16.10% improvement which was slightly higher than 0.6 and 0.8 which are 13.49% and 11.35% respectively in sample reinforced with grouped columns with diameter 16mm.